SPECTROSCOPIC STUDY OF CATIONIC HEMICYANINE DYES IN LITIDUM DODECYL SULFATE SOLUTION: Short Communication (Biological Sciences - PJSIR, 2001)
Hemicyanine dyes are effective voltage sensitive probes inbiomembranes (Loew et a11979; EphardtandFromherz 1989).The probing of rapid changes of electrical potential in biologicalmembrane has been studied in the light of spectroscopicbehaviour of these dyes (Ephardt and Fromherz 1993). Thephysical behaviour of surfactant micelle can be viewed uponas a pseudo model for biomembranes to study the interactionsof biological systems with various additives, for instanceanesthesiatics.